2011
DOI: 10.1377/hlthaff.2011.0178
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits Of Health Information Technology: A Review Of The Recent Literature Shows Predominantly Positive Results

Abstract: An unprecedented federal effort is under way to boost the adoption of electronic health records and spur innovation in health care delivery. We reviewed the recent literature on health information technology to determine its effect on outcomes, including quality, efficiency, and provider satisfaction. We found that 92 percent of the recent articles on health information technology reached conclusions that were positive overall. We also found that the benefits of the technology are beginning to emerge in smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
653
1
12

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,067 publications
(722 citation statements)
references
References 23 publications
19
653
1
12
Order By: Relevance
“…5,6,20,21 This study supports prior work demonstrating the capacity of health information technology to improve processes of care and of CCDS to change provider behavior. [22][23][24] Our study found a median benefit of 2.1 % to clinical process-of-care measures, similar to the rate of 3.8 % found in a 2009 Cochrane Review on the effect of CCDS on process of care. In the same Cochrane Review, only 4 of the 32 included studies looked at CCDS tools as a way to reduce unwanted behavior.…”
Section: Discussionsupporting
confidence: 84%
“…5,6,20,21 This study supports prior work demonstrating the capacity of health information technology to improve processes of care and of CCDS to change provider behavior. [22][23][24] Our study found a median benefit of 2.1 % to clinical process-of-care measures, similar to the rate of 3.8 % found in a 2009 Cochrane Review on the effect of CCDS on process of care. In the same Cochrane Review, only 4 of the 32 included studies looked at CCDS tools as a way to reduce unwanted behavior.…”
Section: Discussionsupporting
confidence: 84%
“…Existing empirical literature on the influence of ICT on hospital performance is more extensive than that for the effect of ICT on hospital innovation, but it refers almost exclusively to USA hospitals and the situation in the USA health sector (see, e.g., Buntin et al 2011 for survey of this literature). 5 The group of the USA studies, on which we focus here, examined the impact of ICT use in hospitals on the quality of health care (Agha 2012;McCullough et al 2010), certain patient outcomes , hospital productivity (Lee et al 2012), hospital cost efficiency (PwCW2007), hospital operating costs (Borzekowski 2009) and the efficiency of the utilization of clinicians (Atkinson et al 2006).…”
Section: Ict and Hospital Performancementioning
confidence: 99%
“…1 HIT could also serve as a foundation to enable improvements in clinical care and support initiatives such as the patient-centered medical home. 2 Yet, adoption of electronic health records (EHRs) in ambulatory care has been relatively limited.…”
Section: Introductionmentioning
confidence: 99%